Kemampuan Berpikir Reflektif Siswa Dalam Menyelesaikan Soal Numerasi Konten Geometri Dan Pengukuran Ditinjau Dari Adversity Quotient - Mukti, Ika Prasetya; Rahaju, Endah Budi; Rahadjeng, Budi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to describe the reflective thinking ability of students with AQ climber, camper and quitter in solving numeracy problems in geometry and measurement content. This research is descriptive research with a qualitative approach. The research subjects were six students consisting of two climber students, two camper students and two quitter students. The instruments used include numeracy questions, interview guidelines and ARP questionnaire. The results of this study showed that climber and camper students showed reflective thinking ability: description of experience based on the problem, elaboration of the experience in generating solution strategies, analysis of the experience based on solution, and evaluating the experience based on solution. In students with climber type, this ability appears optimally indicated by reflective thinking activities seen in all indicators. Meanwhile, in camper students, reflective thinking ability did not appear optimally in some components. Quitter students did not show reflective thinking ability in analysis of the experience based on solution.